Readiness to change and pro-health behaviours among students of physical education and other teaching specialisations - Grażyna Kosiba; Maria Gacek; Agnieszka Wojtowicz (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2019)
The aim of the study was to analyse the relationship between the profile of readiness to change and pro-health behaviours as well as physical activity among students of physical education and other teaching specialisation. The study was carried among a randomly selected group of teaching specialisation students (464 females and 143 males). In the research, the following were applied: Inventory of Pro-health Behaviours by Juczyński, the IPAQ and the Readiness to Change Questionnaire. Diversification in pro-health behaviours, level of physical activity and selected features of readiness to change among students of teaching specialisations was demonstrated. In the general population, along with the increase in self-confidence, passion and optimism, the level of health pro-behaviours also increased. Regardless of type of studies, there were significant positive correlations between the level of physical activity and the degree of passion, optimism and boldness. Among students of other teaching specialisations (apart from physical education), a positive relationship was also noted between physical activity and creativity. Among the students of teaching specialisations, a correlation was demonstrated between the level of pro-health behaviours and physical activity as well as the degree of selected features constituting readiness to change.